Peran Sentuhan Gastronomi pada Hidangan Kuliner Nasi Tiwul Khas Trenggalek - Fahmi Izzulhaq; Stella Alvianna; Irany Whindyastiti; Christina Sri Ratnaningsih (Jurnal Perhotelan, Destinasi Wisata, Perjalanan Wisata (Jurnal Tesla), 2023)
Gastronomy, Local Cuisine and Food Tourism are three separate things but touch each other and many of the parameters are the same for the three concepts. Nasi Tiwul or what the Javanese call Sego Tiwul, is synonymous with originating from Trenggalek Regency. This research is a qualitative research in which interviews were conducted with well-defined traditional food buyers and sellers in Trenggalek. The results of interviews with informants prove that sellers are starting to embrace technological developments. The seller's awareness of technology has a significant influence on business development and increased sales of nasi tiwul. This is because the market share is getting wider. In addition, some of the buyers interviewed said that the weakness of the nasi tiwul business in Trenggalek was the lack of promotion. This causes not many people from outside the area who know and are interested in nasi tiwul.